Vortices and Turbulence at Very Low Temperatures - Barenghi, Carlo; Sergeev, Yuri.; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2008)
Recent investigations have highlighted the similarities between turbulence in cryogenic fluids at temperatures close to absolute zero, in particular superfluid helium, and turbulence in ordinary fluids. This book contains lectures on various theoretical and experimental aspects of the problem given by experts at the advanced school “Vortices and Turbulence at Low Temperatures” held at CISM, Udine, in the summer of 2007. The lectures provide an introduction into this rapidly expanding area of research. The book is suitable to PhD students and young researchers starting their career as well as established researchers in either low temperature physics or fluid mechanics who are interested in this problem.
to quantised vortices and turbulence -- Motion of Solid Particles and Flow Visualization in Helium II -- Counterflow Turbulence in He II and Its Decay -- Bose-Einstein condensation and superfluid turbulence -- Turbulence Experiments in Superfluid 3He at Very Low Temperatures -- Classical Turbulence in Cryogenic Helium.
Keywords: Fluid mechanics; Engineering Fluid Dynamics